Introduction to Digital Navigation : Including Fundamentals of Navigation - Olsen, Alexander Arnfinn (Springer Series on Naval Architecture, Marine Engineering, Shipbuilding and Shipping, 2024)
This book focuses on Coastal and Ocean Navigation with an emphasis on digital navigation (using ECDIS) and would be useful to both experienced seafarers as an aide memoire, and also to cadets and trainees embarking on their maritime careers. The text has been developed for modern day ship’s navigator in the ‘digital era’. It is written from the perspective that the reader’s vessel will be navigated using an IMO type-approved electronic chart and display information system (ECDIS) as opposed to traditional chart-based passage planning. As such, the book focuses on the main principles associated with position and direction of the earth's surface, geodesy projects and grids, digital navigation, electronic chart and data information systems, fixing, internal aids to navigation and systems, external aids to navigation, tides and currents, ocean navigation, coastal navigation, pilotage and blind pilotage, anchoring, navigational errors, relative velocity, and bridge organisation and management